Sexual violence on campus : power-conscious approaches to awareness, prevention, and response - Linder, Chris, 1976- (Great debates in higher education., 2018)
In this important book, Linder advances a power-conscious lens to challenge student activists, administrators, educators, and policy makers to develop more nuanced approaches to sexual violence awareness, response, and prevention on college campuses.